Spatial Distribution of DTPA-Extractable Micronutrients in Arid Soils of Jhunjhunun District, Rajasthan - Kumar, Mahesh; Moharana, P C; Raina, P; Kar, Amal (Annals of Arid Zone, 2016)
Based on 252 georeferenced surface soil samples (0-30 cm), the spatial variability of DTPA-extractable micronutrients viz., Zn, Fe, Mn, and Cu, in four major land uses in Jhunjhunun District, has been mapped in a GIS environment, and their adequacy determined as per the criteria followed in the soil testing laboratories. Zn content in soils varied from 0.28 to 3.6 mg kg-1, Fe from 3.2 to 30.4 mg kg-1, Mn from 3.4 to 40.5 mg kg-1 and Cu from 0.12 to 4.8 mg kg-1. About 18% area (106704 ha) of the district is deficient in Zn, and 6.3% area (37346.4 ha) in Fe. Deficiency of Mn and Cu is negligible. Individual micronutrient deficiency is more prominent than deficiency of micronutrients in combinations. A broad positive correlation of the DTPA-extractable micronutrients is found with soil organic carbon and clay, while soil pH and CaCO3 has negative influence on the availability of Zn, Mn and Fe. Key words: Micronutrients, spatial variability, land use, GIS.